PENGARUH PENDEKATAN ANDRAGOGY TERHADAP KEPUASAN BELAJAR PESERTA DIDIK PROGRAM KESETARAAN PAKET C - kartini marzuki kartini (UNIVERSITAS NEGERI MAKASSAR, 2022)
This equality education is an activity carried out in out-of-school education as a sub-system of non-formal education. Participants studying the C package equality program are people who are over 17 years old and even many are employees. As a class attended by adult participants, the design of learning activities is adjusted to the characterization of the age of the students as adults. Therefore, learning satisfaction is considered as one of the factors that must be of concern to the organizers and tutors in the equality program. This research is a quantitative study that reveals whether or not there is an influence of the andragogy approach in learning on the level of student satisfaction. The results of the an researchershow that there is an influence of the andragogy approach on the learning satisfaction of students of the Paket C equality program . Learner Learning Satisfaction in learning based on an andragogy approach in the high category when the tutor always connects the learning material with the learner's experience in his daily persistence.